Factors of Increasing Spiritual and Social Activity of Youth - Jumaboev Nabi Pardaboevich (International Journal on Economics, Finance and Sustainable Development, 2021)
The article is devoted to the analysis of such tasks as the formation of educational values among modern youth, the further development of ideas about a person, family and society, teaching the younger generation to understand their rights and responsibilities through education and upbringing, preserving the national heritage.